Website-based Dental Health Promotion on Night Tooth Brushing Patterns in Junior High School Students - Lili Kurnia Sari; Cahyo Nugroho; Tita Kartika Dewi (Center of Excellent (Pusat Unggulan Iptek), 2023)
Background: According to Riskesdas in 2018at the age of 15-24 years the percentage of correct brushing time is still very less, namely 3.3%. Promotive efforts that can be done are through a health website which contains health information about the importance of a night toothbrush that can change the student's toothbrush pattern. Aim: This study was to the effect of promotive health websites on night brushing patterns for junior high school students in Kawalu City, Tasikmalaya. Methods: pre-experimental design with a one group pretest posttest design on 23 students. Promoting the health website was carried out twice with a pretest on filling out the night toothbrush pattern questionnaire. Results: Wilcoxon test obtained the night toothbrush pattern with a value of p = 0.000 (p< 0.05), which means that there is a significant effect of Health website on night brushing patterns for junior high school students in Kawalu, Tasikmalaya city. Conclusion: Website-based dental health promotion is effective in improving night brushing patterns in junior high school students.